2021
DOI: 10.1371/journal.pone.0253720
|View full text |Cite
|
Sign up to set email alerts
|

A normative database of A-scan data using the Heidelberg Spectralis Spectral Domain Optical Coherence Tomography machine

Abstract: Purpose To develop the first normative database of macular and circumpapillary scans with reference values at the level of the A-scan using the Heidelberg Spectralis Optical Coherence Tomography (OCT) machine. Methods This study is a retrospective cross sectional analysis of macular and circumpapillary OCT scans of healthy individuals. All participants had a full ophthalmic examination, including best corrected visual acuity, intraocular pressure, biomicroscopy, posterior segment examination and OCT scan. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…OCT showed a bilateral, mild, but nearly circular reduction of the peripapillary RNFL thickness ( Figure 3 B,C). Likewise, her macular ganglion cell layer volume was mildly reduced to a mean of 0.78 mm³ and 0.83 mm³ on the right and left eye, respectively ( Figure 3 D,E; mean in the respective age group = 1.12 mm³, 5th percentile = 0.99 mm³, 95th percentile = 1.25 mm³; reference data from Meyer et al (2021) [ 25 ]). Automated static perimetry and visually evoked potentials were unremarkable.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…OCT showed a bilateral, mild, but nearly circular reduction of the peripapillary RNFL thickness ( Figure 3 B,C). Likewise, her macular ganglion cell layer volume was mildly reduced to a mean of 0.78 mm³ and 0.83 mm³ on the right and left eye, respectively ( Figure 3 D,E; mean in the respective age group = 1.12 mm³, 5th percentile = 0.99 mm³, 95th percentile = 1.25 mm³; reference data from Meyer et al (2021) [ 25 ]). Automated static perimetry and visually evoked potentials were unremarkable.…”
Section: Resultsmentioning
confidence: 78%
“…( D , E ) GCL volume quantification from macular OCT. Note the mild reduction in GCL volume (mean in the respective age group = 1.12 mm³, 5th percentile = 0.99 mm³, 95th percentile = 1.25 mm³; reference data from Meyer et al (2021) [ 25 ]).…”
Section: Figurementioning
confidence: 99%
“…Grover et al [ 29 ] studied the CMT on 36 Caucasian individuals with ages ranging from 20 to 84 years and found a mean CMT of 271.4 ± 19.6 µm. Also, Meyer et al [ 30 ] studied the MV in addition to CMT on a similar study group (25 subjects with ages ranging from 69 to 88 years) and observed a CMT of 270.17 µm. In respect to the OCT measurements, for research purposes we chose a cut-off value for CMT of 270 µm and 8.59 µm 3 for MV because of the similarity between our study sample (Caucasian subjects with similar ages) and the previously cited studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a reduced pRNFL thickness may or may not have a strong relation to clinical visual sensory function and thus should not be taken as absolute evidence of visual dysfunction. In recent years, Yanni et al [ 18 ] and Bhoiwala et al [ 12 ] published normative pediatric values for macular thickness, pRNFL thickness, and retinal thickness in healthy North American children using Spectralis and Optovue SD-OCT device, respectively: average global pRNFL thickness in children aged 5–15 years was 107.6 µm using Spectralis SD-OCT, while in patients of 5 years of age mean pRNFL was 103.93 ± 10.59 µm, which is significantly higher than normative data for healthy white adults [ 19 ]. According to the literature, the mean pRNFL thickness decreases approximately by 1.5 μm per decade in the healthy eyes of adults.…”
Section: Discussionmentioning
confidence: 99%